ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA USAHA KECIL DAN MENENGAH KABUPATEN MANOKWARI - Rahayu, Yuyun Puji; Dedi, Selmi; Toyib, Jein (BISMA: Jurnal Bisnis dan Manajemen, 2019)
The existence of Small and Medium Enterprises (SMEs) has a strategic role to support local economic growth and create employment. This study aims to analyze the influence of company resources, business capabilities, and business strategy on the performance of SMEs in Manokwari Regency. This research is a descriptive study applying survey approach. Data were obtained from interviews and questionnaires distribution. Using accidental and proportional sampling, the collected sample was consisted of 100 SMEs in Manokwari Regency. The results showed that company resources and business capability had a significant influence on the performance, while business strategy did not affect the performance of SMEs in Manokwari Regency. Keywords : SMEs, company resources, business capability, business strategy.